Advanced synthesis of highly crystallized hexagonal boron nitride by coupling polymer-derived ceramics and spark plasma sintering processes—influence of the crystallization promoter and sintering temperature. (19th November 2018) - Li, Yangdi; Garnier, Vincent; Journet, Catherine; Barjon, Julien; Loiseau, Annick; Stenger, Ingrid; Plaud, Alexandre; Toury, Bérangère; Steyer, Philippe
Abstract: Hexagonal boron nitride nanosheets (BNNSs) are promising 2D materials due to their exceptional chemical and thermal stabilities together with their electrical insulation properties. A combined synthesis method involving the polymer-derived ceramics (PDCs) route and the spark plasma sintering (SPS) process is proposed, leading to well-crystallized and pure layered h-BN crystals, prone to be exfoliated into large BNNSs. Here we focus more specifically on the influence of two key parameters of the process to be optimized: the Li3 N concentration (0–10 wt%) and the SPS temperature (1200 °C–1950 °C). The presence of Li3 N, added as crystal promoter in the pre-ceramic powder, significantly improves the crystallinity level of the product, as evidenced by XRD, SEM and Raman spectrometry. SPS temperature strongly modifies the size of the resulting h-BN flakes. The influence of SPS temperature on both purity and crystallinity is studied using cathodoluminescence. h-BN flakes larger than 200 μ m 2 (average flake area) are obtained. Few-layered BNNSs are successfully isolated, through exfoliation process.